STUDY OF THE STABILITY IN REAL TIME OF CRYOPRESERVED STRAIN BANKS (2004)
The stability in real time of four strains cryopreserved in 10% v/v of glycerol was evaluated during a 6-month period. The strains studied were Escherichia coli, Bacillus subtilis, Saccharomyces cerevisiae and Aspergillus niger. The Master Cell Bank (MCB), cryopreserved at -70ºC and -20ºC, was activated using two thawing protocols, a fast one (F) and a slow one (S). A better cell recovery was achieved with the -70ºC (F) protocol reaching a viability for Escherichia coli of 97.6% in the first 48 hours (p: 7.2x10-4). The viability was retained in the 4th (p: 1.5 x10-4), 5th (p: 4.6 x10-3) and 6th months (p: 1.9 x10-2). Bacillus subtilis retained a viability of 92.5% after the 2nd (p: 4.7x10-4), 4th (p: 1.76x10-1), 5th (p: 3.4x10-5) and 6thmonths (p: 3x10-2). Saccharomyces cerevisiae demonstrated a viability of 95% in the second month (p:9x10-3) and for Aspergillus niger, the viability was 94.8%, in the first 48 hours (p: 7.2 x10-4) and after the 4th month (p: 2.79x10-2). With the other protocols, -20ºC F and S, some changes in viability were observed due probably to the formation of eutectic mixtures, nucleation and re-crystallization processes. The Master Bank microbial purity was maintained at 100% during the time of the study.